Arthroscopic-assisted reduction and fixation of calcaneal fractures using sustentaculum tali and medial wall screws - Tang, Zeyin; Zhang, Shuo; Zhu, Nan; Huai, Chaoyue; Wang, Xinru; Zhan, Junfeng; Jing, Juehua (Frontiers in Surgery, 2025)
ObjectiveThis study retrospectively analyzed the clinical efficacy and safety of arthroscopy-assisted reduction and internal fixation in the treatment of displaced intra-articular fractures of the calcaneus (Sanders type II and III).MethodsConducted at The Second Affiliated Hospital of Anhui Medical University, this retrospective study analyzed 60 consecutive patients with displaced intra-articular calcaneal fractures (DIACFs) admitted between January 2021 and February 2023. All patients underwent arthroscopically-assisted minimally invasive reduction and fixation with sustentaculum tali screws plus medial wall support screw. Outcomes were tracked preoperatively, postoperatively, and at final follow-up, encompassing radiographic metrics (Böhler angle, Gissane angle, calcaneal width, calcaneal height) and clinical scores (AOFAS Ankle-Hindfoot Scale, VAS). Pre-to-postoperative changes were analyzed using paired t-tests (normal distribution) or Wilcoxon signed-rank tests (non-normal distribution), with P < 0.05 considered significant.ResultsAll 60 patients completed a minimum 12-month postoperative follow-up. Fracture union was achieved in all cases with no loss to follow-up. Postoperative CT and x-ray imaging confirmed: satisfactory calcaneal morphological restoration, maintained reduction without significant loss between postoperative and final measurements (P > 0.05). At the end of the postoperative follow-up, The major complication rate was 0/60 cases (95% upper limit ≈ 4.9%); AOFAS score was 88.2 ± 3.9, with a 95% CI of 87.2–89.2; VAS score was 0.23 ± 0.57, with a 95% CI of 0.08–0.38.ConclusionArthroscopically assisted reduction and internal fixation using calcanar screws and medial wall support screws is a feasible and effective surgical strategy for the treatment of Sanders type II and type III intra-articular calcaneal fractures.